Electrochemical performance of hydrothermally synthesized rGO based electrodes. (September 2019) - Lyu, J.; Mayyas, M.; Salim, O.; Zhu, H.; Chu, D.; Joshi, R.K.
Abstract: Reduced graphene oxides (rGOs) have attracted substantial interest as potential carbon electrode material for energy storage applications. Yet, the utility of this material for these applications is governed by its stability, composition (C, H, O), surface area and porosity. Tuning the structure and porosity of the rGO sheets is possible by varying the synthesis conditions. Herein, we report the growth of rGO sheets onto a metal substrate from a diluted GO suspension. The prepared electrode material demonstrated a stable electrochemical performance with a supercapacitance value of 195 F g −1 at 1 mV s −1 and low real impedance with good stability and integrity after 4000 cycles of continuous charge-discharge in 1 M KOH electrolyte. This performance is attributed to the unique architecture of the rGO based electrodes which are composed of nano-channels between the sheets that allow rapid diffusion of charge carriers and ions for electrochemical interactions. The observations reported in this work create a new understanding of the structure-stability-performance trade-off in rGO and layout the foundation for further investigations on their sustainable utilization in energy storage applications. Graphical abstract: Image 1 Highlights: A facile set-up for hydrothermal method was utilized to prepare stable rGO with diluted GO solution as precursor. Stability and structure of hydrothermally prepared rGO based electrodes are discussed. Ionic diffusion through the matrix of the rGO/electrode system was studied using the impedance spectroscopy. Supercapacitor behaviour has been studied using rGO electrodes.